Peeking Behind the Curtain: Unboxing Science Teacher Educators Subjectivities in Continuous Professional Development Programmes - Galdames-Poblete, S (EDICIONES UNIV VALPARAISO, 2023)
A large body of knowledge agrees about the central contribution of continuous professional development (CPD) programmes to support curriculum reform. Nonetheless, achieving outstanding CPD is challenging, as it demands financial resources, time, talent, and a well-defined university-school alliance. In Latin-American, there is growing concern about the university-school relationship, mostly related to the CPD of teachers, having arguments addressing and challenging the distance between educative levels. In Chile, the relationship university-school is posed in institutional discourses as a desirable goal of professional development, but still, its importance is less recognised in practice. In this scenario, the role of the teacher educators regarding their own professional development is frequently silenced by the university s conditions. Promoting, creating and implementing CPD demands a critical examination of the work of teacher educators and the context in which these initiatives are first thought. Considering the teacher educators subjectivity in higher education is barely explored in the teacher education literature leaves the question of who are the teachers educators involved in CPD programmes?Using a qualitative approach and a dialogical strategy, this study draws data from a recent project funded by the Ministry of Education anonymously called National Inquiry-Professional Development (NIPDE). NIPDE had four main topics: (1) big ideas of science education, (2) contextualisation to the local territory, (3) community of learning, and (4) scientific inquiry. We study 11 design meetings of a university team/teacher educators leading a science CPD programme. The university team was formed by 12 professionals (including one of the article s authors) from different areas related to science education. The meetings were transcribed verbatim. Data were initially coded, having as a backdrop the notion of border and figured worlds in the relationship academia-school -within academia too -considering the interactions among the university team during the design meetingsFindings show salient features of the teacher educators subjectivity produced around the interaction between the school and the higher education sector, their relationship among themselves, the conditions of the university, and their perception of schoolteachers. Teacher educators positioned them(our)selves as experts due to preconceived knowledge imbalances between teacher educators and schoolteachers. These subjectivities shifted during the CPD course, resulting in different forms of engagement. This article attempts to expand narrow understandings of teacher educators, whose professional development is usually not considered, restricted to mainly giving the necessary support to guarantee that the curriculum and its changes are implemented appropriately . Implications to policy and practices are discussed.